Eliza undermined : the romanticisation of Shaw's Pygmalion : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in English at Massey University, Turitea campus, New Zealand - McGovern, Derek John; McGovern, Derek John (Massey University, 2011)
Few twentieth-century plays have been adapted into as many media as Bernard Shaw’s Pygmalion. First performed on stage in 1913, it was published in book form (1916), turned into a series of screenplays and films (1934–38), modified for a stage musical (My Fair Lady, 1956) and for a film musical (My Fair Lady, 1964). In addition, the original text was revised in 1939 and 1941. This thesis examines the ways in which the play’s core themes have been reworked for these adaptations through a nexus of interpreters’ and adapters’ intentions, the formal conventions of the various media, and the interventions of Shaw himself. Throughout his screenplay and (stage) textual revisions, Shaw strove to emphasise the anti-romantic nature of the original play and its central concerns of class, independence, and transformation. On the stage, in Shaw’s retelling of the Pygmalion myth, the point was not that the “creator” (Higgins) and “creation” (Eliza) fall in love, but rather that the latter achieves independence from her autocratic Pygmalion. Marriage between the two, Shaw declared, was unthinkable. To his dismay, however, audiences and critics alike inferred otherwise, often influenced by the interventions of the play’s interpreters. So via his prose sequel of 1916 and his 1934–38 screenplay, Shaw emphasised a marital future for Eliza with Freddy Eynsford Hill (a minor character in the original play) in an attempt to satisfy these expectations of romance without compromising Eliza’s or Higgins’s independence. Despite this, filmmakers continued to imply a Higgins–Eliza romance, whereupon Shaw responded by changing the ending of his stage text and aggrandising Freddy’s role for his 1941 “definitive” version. Ultimately, however, this damaged the original play’s structural and tonal unity. Oddly enough, the musical adaptations of Pygmalion that appeared after Shaw’s death were more successful in portraying Freddy as a credible romantic foil to Higgins. My Fair Lady differs significantly from Shaw’s Pygmalion, however, by suggesting that Higgins’s independence undergoes a transformation as profound as Eliza’s. This thesis explores the life cycle of Pygmalion and the tensions of authorship caused by adaptations, and, in particular, Shaw’s attempts to assert his own conception of the text, and others’ determination to modify it.
Keywords: My Fair Lady; George Bernard Shaw; Romance in literature; Authorship; Adaptations